Rolled copper foil, copper-clad laminate, method for manufacturing copper-clad laminate, method for manufacturing flexible printed wiring board, and method for manufacturing electronic component

By performing heat treatment of the rolled copper foil at 370°C and 1 second and optimizing the Ag content, the problem of lower bending in the lamination method is solved, and higher bending and stability are achieved. It is suitable for the manufacturing of flexible printed circuit boards. .

CN119256109APending Publication Date: 2025-01-03JX NIPPON MINING & METALS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042414.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-04
Filing Date
2023-06-01
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When manufacturing copper-clad laminated plates using lamination method, due to the rapid heating rate of the material during heat treatment, the growth of crystal nuclei in multi-direction orientation is inhibited, and the bending ability is reduced, which lacks the ability to provide high bending ability in a short time. calendered copper foil.

Method used

By performing heat treatment on the calendered copper foil with a heating temperature of 370°C and a heating time of 1 second, the arithmetic average value of the Cube area ratio reaches more than 77.0%, combined with the Ag content of 180 to 360 ppm and the thickness of 4 to 35 μm. Optimize the Cube orientation and crystal grain size after heat treatment to improve bending.

Benefits of technology

It is achieved to provide higher bending properties, stability and excellent bending properties than before under lamination manufacturing conditions, and avoid the negative impact of heating conditions on bending properties during the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148551540000161
    Figure BDA0005148551540000161
  • Figure BDA0005148551540000171
    Figure BDA0005148551540000171
  • Figure BDA0005148551540000181
    Figure BDA0005148551540000181
Patent Text Reader

Abstract

Provided is a rolled copper foil which has higher bendability than in the prior art when the rolled copper foil is FPC-formed by manufacturing a CCL by a lamination method. The rolled copper foil contains 99.9% by mass or more of Cu, with the remainder comprising unavoidable impurities, and when heat treatment is performed at a heating holding temperature of 370 DEG C and a heating holding time of 1 second, the arithmetic mean value of the Cube area ratio obtained by measuring three points in total, i.e., one arbitrary point and two points spaced apart from the point at an equal distance of 5 mm in the direction perpendicular to the rolling direction is 77.0% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rolled copper foil, a copper-clad laminate, a method for manufacturing the copper-clad laminate, a method for manufacturing a flexible printed circuit board, and a method for manufacturing an electronic component. Background Art

[0002] Flexible printed circuits (FPCs) are made by bonding a metal conductive layer to a flexible insulating substrate such as a resin film. Usually, copper foil is used as the conductive layer, and in applications where flexibility is particularly required, rolled copper foil with excellent flexibility is used.

[0003] The usual FPC manufacturing steps are as follows. First, copper foil is bonded to a resin film. Regarding bonding, there is a method of coating a varnish containing a precursor of a polyimide resin on the copper foil and applying a heat treatment to imidize (casting method), and a method of overlapping and laminating a resin film having adhesive force with the copper foil (lamination method). The copper foil with a resin film bonded by these steps is called a copper clad laminate (CCL). After that, a circuit is formed by etching to complete the FPC.

[0004] As mentioned above, the rolled copper foil for FPC needs to be bendable. In order to provide a rolled copper foil for FPC that is easy to anneal at the curing temperature of the resin adhesive and has excellent bending resistance (bending fatigue life) after annealing, it is proposed to make the final cold working degree more than 90%.

[0005] Prior art literature:

[0006] Patent Literature

[0007] Patent document 1: Japanese Patent Application Laid-Open No. 4-228553. Summary of the invention

[0008] Technical problems to be solved by the invention:

[0009] It is worth mentioning that in CCL manufacturing, in recent years, due to the shortening of manufacturing steps and the increased awareness of environmental issues, the casting method is sometimes not required, but a lamination method that performs heat treatment in a shorter time is required. However, when the lamination method is used, since the heating rate of the material during the heat treatment is relatively fast, crystal nuclei oriented in multiple directions are formed and grow, which inhibits the development of cubic orientation. Therefore, compared with the casting method that takes a long time to perform heat treatment during stacking, there is a tendency for the lamination method to reduce bending. Therefore, there is a demand for copper foil to have higher bending even if it is heat treated in a short period corresponding to the lamination method.

[0010] Therefore, in one embodiment of the present invention, an object is to provide a rolled copper foil having higher bendability than before when a CCL is manufactured by a lamination method and converted into an FPC.

[0011] Solutions to technical problems:

[0012] The inventors of the present invention have conducted various studies and found that the Cube area ratio when the rolled copper foil is heat treated has an effect on the bendability when it is made into FPC. In addition, when the heat treatment is carried out at a heating holding temperature of 370°C and a heating holding time of 1 second, the arithmetic mean of the Cube area ratio is made to be 77.0% or more, and a rolled copper foil with higher bendability than before can be obtained, and the invention as exemplified below is created. [1]

[0014] A rolled copper foil containing 99.9% by mass or more of Cu, the remainder being inevitable impurities, wherein when the rolled copper foil is heat treated at a heating holding temperature of 370° C. and a heating holding time of 1 second, the arithmetic mean of the Cube area ratio measured at three points in total, namely, at one arbitrary point and at two points in a direction perpendicular to the rolling and equally spaced by 5 mm from the point, is 77.0% or more. [2]

[0016] The rolled copper foil according to [1], further comprising 180 to 360 mass ppm of Ag. [3]

[0018] The rolled copper foil according to any one of [1] to [2], wherein the thickness is 4 to 35 μm. [4]

[0020] A copper-clad laminate having a rolled copper foil with a Cube area ratio of 77.0% or more. [5]

[0022] A method for producing a copper-clad laminate, comprising the step of bonding the rolled copper foil according to any one of [1] to [3] to a substrate, and performing a heat treatment in the step. [6]

[0024] A method for manufacturing a flexible printed wiring board, comprising the step of using the copper-clad laminate manufactured by the method for manufacturing a copper-clad laminate according to [5] as a material to form a circuit. [7]

[0026] A method for manufacturing an electronic component includes the step of manufacturing an electronic component having a flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board according to [6].

[0027] Effects of the invention:

[0028] According to one embodiment of the present invention, it is possible to provide a rolled copper foil having higher bendability than before when a CCL is manufactured by a lamination method and converted into an FPC. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a schematic diagram of a jig used in heat treatment of rolled copper foil.

[0030] Figure 2 This is a schematic diagram showing a measurement method of the IPC sliding bending test in Reference Examples 1 to 4 and Comparative Example 4.

[0031] Figure 3 This is a graph drawn based on Reference Examples 1 to 4 and Comparative Example 4, with the horizontal axis representing the arithmetic mean of the Cube area ratio after various CCL heat treatments and the vertical axis representing the number of IPC sliding bends. DETAILED DESCRIPTION

[0032] The present invention is not limited to the embodiments described below, and the components can be modified and embodied within the scope of the gist thereof. In addition, various inventions can be formed by appropriately combining a plurality of components disclosed in the embodiments.

[0033] It should be noted that the "Cube orientation" in this specification refers to the orientation of grains in which the {001} plane is parallel to the rolling surface and the <100> crystal direction is parallel to the rolling direction (RD), and is represented by the index {001} <100>. In addition, the "Cube area ratio" represents the area ratio of the Cube orientation {001} <100>. In addition, the "rolling direction" refers to the direction parallel to the direction in which the rolled object passes between the paired working rolls. In addition, the "rolling perpendicular direction" refers to the direction perpendicular to the rolling direction in the rolling surface.

[0034] [1. Rolled copper foil]

[0035] (Component)

[0036] In one embodiment, the rolled copper foil of the present invention contains 99.9 mass % or more of Cu, with the remainder being composed of inevitable impurities. In another embodiment, the rolled copper foil may be composed of pure Cu.

[0037] In one embodiment, the rolled copper foil may contain 180 to 360 ppm by mass of Ag as an alloy element based on the viewpoint of obtaining a higher bendability than before when FPC is formed and controlling the appropriate recrystallization temperature. In particular, it is preferred that the tough-pitch copper (TPC) of JIS-H3100 (C1100) standard or the oxygen-free copper (OFC) of JIS-H3100 (C1020) contain the above-mentioned additive elements.

[0038] When the Ag content exceeds 360 mass ppm, under the influence of the increase in the recrystallization temperature of the rolled copper foil, even if the heat treatment in the lamination method is implemented, the recrystallization is sometimes insufficient. If it is assumed that there are unrecrystallized grains remaining in the rolled copper foil, the bendability of the FPC will be significantly reduced. In addition, if the Ag content is above 180 mass ppm, the amount of rolling strain introduced will increase, so the cubic texture after the CCL heat treatment is easy to grow, and the bendability is easy to increase.

[0039] It should be noted that the upper limit of the oxygen content in the rolled copper foil is, for example, 500 mass ppm or less. In addition, the lower limit of the oxygen content in the rolled copper foil is, for example, 0 mass ppm or more. Based on the viewpoint of reducing the amount of copper oxide (CuO) in the material, the oxygen content is preferably 50 mass ppm or less, and it is generally believed that copper oxide (CuO) will have an adverse effect on the bendability of the FPC.

[0040] The composition of the rolled copper foil of the present invention can be measured by fluorescent X-ray analysis as a dry analysis. Specifically, the fluorescent X-ray analysis is measured using Simultix14 manufactured by Rigaku Corporation. The analysis surface can use a surface that has been cut or mechanically polished in a manner such that the surface maximum height roughness Rz (JIS B0601: 2013) is 6.3 μm or less. In the case of taking a sample for analysis from the molten metal in the melt casting process of the manufacturing process of the rolled copper foil, after casting into a shape of 30 to 40 mmΦ and a thickness of about 50 to 80 mm, it is cut into a thickness of about 10 to 20 mm, and the cut surface is used as the analysis surface. The analysis surface is repeatedly cut or mechanically polished until the surface maximum height roughness Rz (JIS B0601: 2013) is 6.3 μm or less.

[0041] It should be noted that the composition of rolled copper foil can be determined by using not only fluorescent X-ray analysis but also ICP emission spectrometry as a wet analysis. Specifically, it can be determined using an ICP emission spectrometry device (ICP-OES) SPS3100 manufactured by Hitachi High-Tech Sciences. In the case of ICP emission spectrometry, the sample is dissolved in a nitric acid aqueous solution (nitric acid: water = 1:1 by volume ratio) and diluted for use.

[0042] (Cube area ratio)

[0043] In one embodiment of the rolled copper foil of the present invention, the arithmetic mean of the Cube area ratio is 77.0% or more when measured by the method described below by heating the rolled copper foil at a heating holding temperature of 370° C. and a heating holding time of 1 second in a dryer.

[0044] Specifically, a portion of rolled copper foil was used as a sample, and the sample was wrapped with a sheet of rolled copper foil (thickness: 0.006 mm) to form a sealed body in order to prevent oxidation in the air atmosphere or to prevent bending and wrinkling when taken out of a desiccator.

[0045] Next, the temperature was maintained at 380°C in a flask (DRH453WA manufactured by Advantech Toyo Co., Ltd.). Figure 1 The clamp 100 shown is heated to a temperature of 370°C and maintained for 1 hour. It should be noted that the clamp 100 comprises: a first clamping portion 110 in a rectangular shape, which has a first clamping surface 112 for clamping a sealed body wrapped with a rolled copper foil; a second clamping portion 120 in a rectangular shape, which has a second clamping surface 122 for clamping the sealed body; a hinge portion 130 connected to one end of the first clamping portion 110 and one end of the second clamping portion 120; and a handle 116 is installed on a surface 114 of the first clamping portion 110 on the opposite side of the first clamping surface 112.

[0046] After the temperature of the fixture 100 reaches 370°C and is maintained for 1 hour, the dryer is opened and immediately a metal hook is used on the handle 116 of the fixture 100 in the dryer to pull the first clamping surface 112 away from the second clamping surface 122. After the seal is placed on the second clamping surface 122, the first clamping surface 112 is quickly brought close to the second clamping surface 122 by using a hook on the handle 116, and the seal is clamped by the first clamping surface 112 and the second clamping surface 122. After the seal is heat treated for 1 second with the fixture 100, the first clamping surface 112 is quickly pulled away from the second clamping surface 122 by using a hook on the handle 116, so that the seal is not clamped. That is, the heat treatment time of 1 second means the time from when the fixture 100 clamps the seal to when it is no longer clamped. Then, the seal is quickly taken out of the dryer and placed in the atmosphere for cooling. After cooling, the sample was taken out from the sealed body. It should be noted that the conditions of the jig 100 and the sealed body are as follows.

[0047] <Each condition>

[0048] Fixture

[0049] Weight of handle: 73.8g

[0050] Volume of the first clamping part: 68.64 cm 3 (width 15.6cm x depth 4.4cm x height 1.0cm)

[0051] Weight of the first clamping part: 661.4g

[0052] Material of the first clamping part: Tough copper (JIS H 3100 (C1100))

[0053] Volume of the second clamping part: 68.64 cm 3 (width 15.6cm x depth 4.4cm x height 1.0cm)

[0054] Material of the second clamping part: Tough copper (JIS H 3100 (C1100))

[0055] Sealing body

[0056] Size of seal: Width 50mm x Depth 70mm x Thickness 0.024mmt (When the thickness of the target sample is 0.012mmt)

[0057] Size of the sample (rolled copper foil): 20 mm in width x 20 mm in depth

[0058] The speed at which the Cube orientation develops under the specified heat treatment conditions is relatively fast, and the rolled copper foil with a Cube area ratio of more than the specified value is difficult for dislocations to accumulate toward the crystal grain boundaries in the material when bent. As a result, the generation of cracks that cause breakage is suppressed, so the bendability is excellent, for example, stable bendability that does not depend on the heating conditions when manufacturing copper-clad laminates can be obtained. The arithmetic mean value of the above-mentioned Cube area ratio has a lower limit of 77.0% or more, preferably 80.0% or more. On the other hand, the arithmetic mean value of the above-mentioned Cube area ratio has an upper limit of 100.0% or less.

[0059] The inventors have found that in order to improve the arithmetic mean of the Cube area ratio after heat treatment, it is important to control the average grain size after final annealing and the processing degree of final cold rolling. The conditions of the average grain size after final annealing and the processing degree of final cold rolling are described below and will not be repeated.

[0060] (Measurement method of cube area ratio)

[0061] Next, an example of a method for measuring the Cube area ratio is described. The area ratio of the Cube orientation {001}<100> is measured by EBSD on the surface of a sample of rolled copper foil that has been heat treated at a heating holding temperature of 370°C and a heating holding time of 1 second as described above. Here, EBSD (Electron Back Scatter Diffraction) refers to a technique for analyzing the crystal orientation using the reflected electron Kikuchi line diffraction (Kikuchi pattern) generated when an electron beam is irradiated on a sample in a SEM (Scanning Electron Microscope).

[0062] Electrolytic polishing was performed according to the following electrolyte and test conditions. After removing a thickness of about 1 μm from the sample surface, an observation range of 1000 μm×1000 μm arbitrarily set in a manner with one side of the observation field parallel to the rolling direction was scanned using a step size of 3 μm to measure the crystal orientation distribution.

[0063] The measurement is performed at any one point and at two points which are 5 mm apart from the point in the direction perpendicular to the rolling. It should be noted that if the arithmetic mean of the Cube area rate measured at any one point and at two points which are 5 mm apart from the point in the direction perpendicular to the rolling is 77.0% or more, the rolled copper foil as a whole tends to have higher bendability. The reason is that, although the manufacturing conditions will produce some deviations to a certain extent in the manufacturing step, the Cube area rate measured after the rolled copper foil obtained by the manufacturing step is subjected to heat treatment under prescribed conditions is roughly controlled within the required range. Therefore, when the arithmetic mean of the Cube area rate at any one point and at two points which are 5 mm apart from the point in the direction perpendicular to the rolling is 77.0% or more, although there is a possibility that a part of the rolled copper foil has a portion of the Cube area rate with an arithmetic mean less than 77.0%, it can be assumed that there are not so many such portions, and most of them have become the required metal structure, which can solve the technical problem of the present invention.

[0064] Furthermore, due to the manufacturing and processing of rolled copper foil (for example, cutting of samples for measurement, etc.), there will be abnormal parts such as a part with extremely many holes, foreign matter attached, and rolling stripes. When measuring the Cube area rate, the measurement position should be set to avoid the position corresponding to the abnormal part. By using SEM (observation magnification: 100 times) to observe the sample before electrolytic polishing, etc., the abnormal part can be grasped. When the measurement position overlaps with the abnormal part, avoid the abnormal part and measure a total of 3 points.

[0065] <Preparation of electrolyte solution (an example)>

[0066] 250ml distilled water

[0067] Phosphoric acid 125ml

[0068] ·Urea 2.5g

[0069] ·Ethanol Grade 1 125ml

[0070] 1-Propanol 25ml

[0071] <Electrolytic polishing conditions>

[0072] Applied voltage: 10V

[0073] Electrolysis time: 10 seconds

[0074] <EBSD measurement conditions, etc.>

[0075] ·SEM conditions

[0076] Equipment: Scanning electron microscope manufactured by Hitachi, Ltd. (SU-70 or equivalent)

[0077] Type of electron gun: Electrolytic emission electron gun (Schottky type)

[0078] Electron gun emitter: ZrO tungsten cathode

[0079] Type of objective lens: External lens type

[0080] Focus correction: Yes (dynamic focus: 24)

[0081] Electron beam conditions

[0082] Accelerating voltage: 15 kV

[0083] Working distance: 15mm

[0084] Observation magnification: 90 times

[0085] ·EBSD device conditions

[0086] Detector: Digital CCD camera manufactured by TSL Solutions Co., Ltd.

[0087] Data processing conditions

[0088] Data collection software: OIM Data Collection manufactured by TSL Solutions Co., Ltd.

[0089] Phase: Copper

[0090] CCD camera pixel count: 1394 × 1040 pixels

[0091] Binning (pixel combination): 8×8

[0092] Exposure: 8 milliseconds

[0093] Gain: 0.9~0.95

[0094] Background processing: Yes

[0095] Scanning method of measuring points: Hexagonal grid

[0096] Hough transform

[0097] (1) Hough Type: Classic

[0098] (2) Hough Resolution: Low

[0099] (3) Classic Hough

[0100] Convolution Mask: 9×9

[0101] Min Peak Magnitude: 5

[0102] Min Peak Distance: 23

[0103] Peak Symmetry: 0.75

[0104] Vertical Bias: 0

[0105] (4) General Parameter

[0106] Binned Pattern Size: 120

[0107] Theta Step Size: 1°

[0108] Rho Fraction: 90%

[0109] Max Peak Count: 8

[0110] Min Peak Count: 3

[0111] Then, the crystal orientation density function is analyzed, and the area of ​​the crystal grains with an orientation within 15° of the Cube orientation is divided by the measured area to obtain the area ratio. The above measurement data are collected using OIM Data Collection manufactured by TSL Solutions Co., Ltd., and the data analysis uses OIM Analysis V8 manufactured by TSL Solutions Co., Ltd. It should be noted that the information obtained in the orientation analysis of EBSD includes the orientation information of the depth of the electron beam entering the sample by 10nm, but it is small enough compared to the measurement range, so it is recorded as the area ratio.

[0112] <Data analysis conditions of OIM Analysis V8>

[0113] New Map window

[0114] Map Style

[0115] Grayscale: Select <None>.

[0116] Color Coded: Select Crystal Orientation. Boundaries

[0117] Second Partition: Select <None>.

[0118] ·Crystal Orientation window (screen displayed when you click Edit in Color Coded in Map Style window)

[0119] Representation: Select Euler Angles (Bunge).

[0120] Enforce Orthotropic Sample Symmetry checkbox: Check.

[0121] Add Crystal Orientation Range window (screen displayed when you click Add in the CrystalOrientation window)

[0122] Orientation tag

[0123] Phase: Select Copper.

[0124] Euler Angles

[0125] hkl input values: 001

[0126] Input values ​​of uvw: 100

[0127] Tolerance Tab

[0128] Minimum input value: 0

[0129] Maximum input value: 15

[0130] The value of Total fraction in the measurement result of Crystal Orientation performed under the above-mentioned setting conditions was used as the Cube area ratio.

[0131] (Average grain size after final annealing)

[0132] In one embodiment of the rolled copper foil of the present invention, preferably, the average grain size before the final cold rolling and after the recrystallization annealing 3 (final annealing) in the manufacturing example described below is greater than 15 μm and less than 35 μm. Generally, the smaller the grain size, the easier it is for the dislocation strain that becomes the driving force of the primary recrystallization during the final rolling to accumulate. Therefore, by making the average grain size before the final cold rolling and after the final annealing greater than 15 μm and less than 35 μm, the cubic texture is very developed during the heat treatment of the rolled copper foil, and the bendability is improved. On the other hand, when the average grain size after the final annealing is more than 35 μm, the dislocation strain is not easy to accumulate during the final rolling, and the shear bands in the rolled structure are easy to become developed. The shear bands are easy to become the generation sites of non-Cube-oriented crystal nuclei during the heat treatment of the rolled copper foil, and the cubic texture is difficult to develop.

[0133] (Method for measuring average crystal grain size)

[0134] Next, an example of a method for measuring the average crystal grain size is described. The average crystal grain size is measured by EBSD on the sample surface after the final annealing.

[0135] Electropolishing was performed under the above conditions. After removing a thickness of about 1 μm from the sample surface, the observation range of 1000 μm × 1000 μm was arbitrarily set and scanned with a step size of 3 μm. After that, the average grain size was measured by the Area Fraction method when the boundary with a crystal orientation difference greater than 5° was regarded as a crystal grain boundary. The above analysis was performed using OIM Analysis V8 manufactured by TSL Solutions Co., Ltd. The measurement conditions of EBSD not shown below are as described above.

[0136] <Detailed settings of OIM Analysis V8 when calculating the average grain size>

[0137] ·Detailed settings of the Partition Properties window

[0138] Grain Size Tab

[0139] Input value for Grain Tolerance Angle: 5

[0140] Minimum Size [points]

[0141] Grains input value: 2

[0142] Anti-grains input value: 2

[0143] Input value for Minimum Confidence Index (minimum CI value): 0

[0144] Check the box for Apply partition before calculation: Check it.

[0145] Include grains at edges of scan in statistics checkbox: Check.

[0146] Twin Boundaries window (screen displayed when you click Define in Partition Properties)

[0147] Check the box for Enforce matching between twin planes(K1)in grain A and grain B: Check.

[0148] Allowed tolerance between twin planes (K1s) [degrees]: 1

[0149] (Twins that are excluded are not specifically specified. Crystal grain boundaries include twins.)

[0150] ·Detailed settings of the New Chart window for calculating the average grain size Type: Grain Size (diameter)

[0151] The value of Area within Average (average value according to the Area Fraction method) in the measurement result of Grain Size performed under the above-mentioned setting conditions is used as the average crystal grain size.

[0152] (thickness)

[0153] In one embodiment, the rolled copper foil has a thickness of 4 to 35 μm, for example. The upper limit of the rolled copper foil thickness is, for example, 35 μm or less, and for example, 18 μm or less, and the lower limit is, for example, 4 μm or more, and for example, 6 μm or more, and for example, 9 μm or more.

[0154] It should be noted that the thickness of the rolled copper foil can be measured by, for example, setting an X-ray generator on one surface side of the rolled copper foil and setting an X-ray detector on the other surface side, calculating the attenuation caused by the rolled copper foil from the measured amount of penetrating X-rays, and converting it into the thickness of the rolled copper foil. For another example, the weight of a 20 cm square rolled copper foil is measured, and the value is calculated by (weight (g) / (density of rolled copper foil (g / cm 3 )×Area of ​​rolled copper foil (cm 2 )) Calculate the thickness of the rolled copper foil (It should be noted that the density of the rolled copper foil is 8.94 g / cm for oxygen-free copper of JIS-H3100 (C1020), for example. 3 For another example, a digital length measuring machine (for example, Micro Digital MH-15M manufactured by Nikon) is used to measure at two or more arbitrary points, and the thickness of the rolled copper foil is calculated from the arithmetic mean of the thicknesses.

[0155] (Manufacturing Example of Rolled Copper Foil)

[0156] As an example of a method for manufacturing rolled copper foil, first, a melting furnace is used to melt raw materials such as copper to obtain a molten metal of the required components. Then, an ingot is manufactured by flowing the molten metal into a casting mold (casting). In order to prevent oxidation loss of copper, melting and casting are preferably carried out in a vacuum or inert gas atmosphere. Afterwards, the following steps are implemented in sequence: homogenization annealing, hot rolling, cold rolling 1, recrystallization annealing 1, surface cutting, cold rolling 2, recrystallization annealing 2, pickling and grinding, cold rolling 3, recrystallization annealing 3 (final annealing), and final cold rolling to form a rolled copper foil having the required thickness and the required characteristics. That is, in the present invention, the rolled copper foil can be said to basically refer to the copper foil after the final cold rolling.

[0157] It should be noted that according to the empirical speculation of the inventors, the arithmetic mean of the Cube area ratio of the rolled copper foil when heat treated at a heating holding temperature of 370°C and a heating holding time of 1 second is greatly affected by the average grain size after the final annealing and the degree of processing of the final cold rolling when manufactured according to the steps described below.

[0158] (Final Annealing)

[0159] In order to improve the arithmetic mean of the Cube area rate when heat treated at a heating holding temperature of 370°C and a heating holding time of 1 second, the conditions for the final annealing are appropriately set. Specifically, the conditions for the final annealing can be appropriately set so that the average grain size after the final annealing is greater than 15 μm and less than 35 μm. The conditions can be varied according to the material composition of the rolled copper foil. Based on the annealing conditions disclosed in this embodiment and the comparative example, those skilled in the art can experimentally seek annealing conditions without too much trial and error.

[0160] (Final cold rolling)

[0161] By performing final cold rolling under the condition that the processing degree is greater than 98% and less than 99%, a rolled copper foil can be obtained. At this time, the thickness of the rolled copper foil is about 4 to 35 μm. It should be noted that the processing degree is defined as processing degree (%) = {(thickness before final cold rolling (mm) - thickness after final cold rolling (mm)) / thickness before final cold rolling (mm)} × 100.

[0162] [2. Method for manufacturing copper-clad laminate]

[0163] In one embodiment of the method for manufacturing a copper-clad laminate of the present invention, the method comprises the step of bonding the rolled copper foil as described above to a substrate. As the substrate, for example, a resin film can be cited. In order to bond the resin film to the rolled copper foil, several methods can be used.

[0164] First, as a method for manufacturing a copper-clad laminate, there is generally a method called a lamination method. According to the lamination method, a copper-clad laminate (CCL) composed of a rolled copper foil and a resin film can be obtained by pressing a resin film (base film) such as polyimide on a rolled copper foil using a thermal treatment device such as a laminator. As an example of a manufacturing method using a lamination method, for example, a 25 μm thick polyimide resin film such as Pixio (trademark) film manufactured by Kaneka Co., Ltd. is overlapped with a roughened surface of a rolled copper foil such as 12 μm, and passed between hot rollers heated to about 300°C to 370°C for lamination and pressing, thereby being able to manufacture a copper-clad laminate. The time (pressing time) of passing between the hot rollers is about 1 second. In the heat treatment using a clamp described above, each step can be performed quickly, so the inventors and others speculate that the heat treatment of the lamination method can be reproduced by the heat treatment using a clamp described above.

[0165] Next, unlike the lamination method, there is a method generally referred to as a casting method as a method for manufacturing a copper-clad laminate. For example, there is a method in which a varnish containing a polyamic acid as a precursor of a polyimide resin is applied to the surface of at least one side of a rolled copper foil, and heat-treated to solidify it, thereby forming a polyimide coating on the surface of at least one side of the rolled copper foil. For example, when a rolled copper foil is laminated on both sides of a polyimide resin film, there is a method of forming a single-sided copper-clad laminate and then crimping the rolled copper foil by hot pressing, and a method of sandwiching a polyimide resin film between two copper foil layers and crimping them by hot pressing. The heat treatment in the casting method is usually carried out under the conditions of 125 to 360°C and 30 to 400 minutes.

[0166] It should be noted that, in the lamination method and the casting method, although an example of using a polyimide resin film is described, it is not limited to this resin film. As the resin film, in addition to the polyimide resin film, for example, polyester, polyethylene terephthalate, polyethylene naphthalate, etc. can be used.

[0167] It should be noted that, typically, in the lamination method, the heat treatment speed is much faster than that in the casting method, and the bendability of the FPC produced is easily reduced compared to the casting method.

[0168] In addition, before laminating the rolled copper foil and the resin film, the rolled copper foil may be subjected to a roughening treatment, thereby increasing the bonding strength between the resin film and the rolled copper foil. For example, the roughening treatment may be performed under the following conditions.

[0169] <Roughening treatment conditions>

[0170] Liquid components: Cu10~20g / L, Co1~10g / L, Ni1~15g / L

[0171] pH: 1-4

[0172] Temperature: 30~50℃

[0173] Current density (Dk): 20~50A / dm 2

[0174] Time: 1 to 5 seconds

[0175] According to this manufacturing method, Cube orientation is developed by the above-mentioned heat treatment, so a copper-clad laminate having a copper foil (rolled copper foil) and a substrate (resin film) with a Cube area ratio of 77.0% or more can be manufactured. It should be noted that the method for measuring the Cube area ratio is the same as the method described above.

[0176] [3. Method for manufacturing flexible printed wiring board]

[0177] In one embodiment, the method for manufacturing a flexible printed circuit board of the present invention includes using a copper-clad laminate manufactured by the method for manufacturing a copper-clad laminate as described above as a material and forming a circuit. At this time, the copper-clad laminate can be used as a material and a circuit can be formed according to a known step to manufacture a flexible printed circuit board (FPC). For example, the following method can be cited: the resist is applied only to the necessary part as the conductor pattern on the rolled copper foil surface of the copper-clad laminate, and then an etching solution is sprayed on the rolled copper foil surface to remove the unnecessary rolled copper foil to form a conductor pattern, and then the resist is peeled off or removed to expose the conductor pattern. After the conductor pattern is formed, a protective covering film is usually attached.

[0178] (use)

[0179] Such an FPC is an FPC used in a movable part in a hard disk, a hinge part and a sliding part of a mobile phone, the inside of a mobile phone, a head of a printer, an optical pickup part, a movable part of a notebook PC, etc. in an electronic component of an electronic device or an electrical device. It should be noted that the method for manufacturing an electronic component may include a step of manufacturing an electronic component having a flexible printed circuit board manufactured by the method for manufacturing a flexible printed circuit board.

[0180] [Example]

[0181] The present invention will be specifically described based on Examples and Comparative Examples. The following Examples and Comparative Examples are only specific examples given to facilitate understanding of the technical content of the present invention, and the technical scope of the present invention is not limited to these specific examples.

[0182] It should be noted that "OFC" in Tables 1, 2, and 3 refers to oxygen-free copper in accordance with JIS H 3100 (C1020) and "TPC" refers to tough pitch copper in accordance with JIS H 3100 (C1100).

[0183] [Examples 1 to 4, Comparative Examples 1 to 3]

[0184] [Manufacture of rolled copper foil]

[0185] First, in Examples 1 to 4 and Comparative Examples 1 to 3, an ingot is melted and cast, and the ingot has an alloy composition shown in Table 1 obtained by adding a specified metal to oxygen-free copper. It should be noted that the Ag content of the ingot is measured by the ICP emission spectrometry method described above. The ingot is processed in the following order to produce a rolled copper foil. It should be noted that the degree of processing in Table 1 is the thickness reduction rate in the final cold rolling, which is calculated by the following formula: degree of processing (%) = {(thickness before final cold rolling (mm) - thickness after final cold rolling (final product) (mm)) / thickness before final cold rolling (mm)} × 100.

[0186] <Steps (1) to (11)>

[0187] (Step 1) Homogenization annealing: The above ingot was heated at 920° C. and maintained for 2.5 hours.

[0188] (Step 2) Hot rolling: The ingot heated at 920° C. was rolled at room temperature to a thickness of 16 mm, and then rapidly cooled to room temperature by water cooling to obtain a strip-shaped metal material.

[0189] (Step 3) Cold rolling 1: rolling to a thickness of 10.5 mm.

[0190] (Step 4) Recrystallization annealing 1: The strip-shaped metal material is heated at 400° C. and maintained for 7.5 hours.

[0191] (Step 5) Surface cutting: The oxide scale layer on the surface is removed by surface cutting.

[0192] (Step 6) Cold rolling 2: rolling to a thickness of 1.5 mm.

[0193] (Step 7) Recrystallization annealing 2: Maintain in a furnace heated to 750°C for 30 to 120 seconds.

[0194] (Step 8) Pickling and polishing: After immersion in a mixed acid of sulfuric acid and hydrogen peroxide, the oxide film on the surface of the material is removed by polishing.

[0195] (Step 9) Cold rolling 3: rolling to a thickness of 0.8 mm.

[0196] (Step 10) Recrystallization annealing 3 (final annealing): The annealing temperature and holding time are adjusted to obtain a specified grain size, and the strip metal material after cold rolling 3 is heated and kept warm respectively. Table 1 records the annealing conditions of each sample. It should be noted that in order to prevent oxidation, the above-mentioned strip metal material is wrapped and sealed with a rolled copper foil (thickness: 33 μm) of fully annealed tough copper (JIS H 3100 (C1100)) to obtain a sealed body placed in a dryer. After heating and keeping warm, the sealed body is taken out of the dryer and placed in an atmospheric atmosphere for cooling. After being placed and cooled, the strip metal material is taken out from the sealed body. Then, the average grain size after the final annealing is determined by the above-mentioned method.

[0197] (Step 11) Final cold rolling: Finishing to a thickness of 0.012 mm (12 μm) to obtain rolled copper foil. In the final cold rolling, the two end sides of the strip metal material in the rolling direction are not fixed (free end state), and the strip metal material is passed between a pair of working rolls and rolled in a manner that tension does not act in a direction parallel to the rolling direction.

[0198] In addition, in Examples 1 to 4 and Comparative Examples 1 to 3, recrystallization annealing 3 was performed at the annealing temperature and holding time described in Table 1.

[0199] [Characteristics evaluation]

[0200] Next, in Examples 1 to 4 and Comparative Examples 1 to 3, a portion of the rolled copper foil obtained by the above-mentioned manufacturing was taken as each sample for measurement, and a piece of rolled copper foil (thickness: 0.006 mm) was used to wrap the sample for measurement by the method described above to form a sealed body. In addition, the temperature of the fixture 100 was maintained at 370°C in a dryer (manufactured by Advantech Toyo Co., Ltd.: DRH453WA) maintained at 380°C for 1 hour. Next, immediately after opening the dryer, the handle 116 of the fixture 100 in the dryer was used with a metal hook to pull the first clamping surface 112 away from the second clamping surface 122. Next, after placing the sealed body on the second clamping surface 122, the hook was quickly used on the handle 116 to make the first clamping surface 112 approach the second clamping surface 122, and the sealed body was clamped by the first clamping surface 112 and the second clamping surface 122. After the seal is heat treated for 1 second using the clamp 100, a hook is used on the handle 116 to quickly pull the first clamping surface 112 away from the second clamping surface 122, so that the seal is not clamped. Thereafter, the seal is quickly taken out of the dryer and placed in the air atmosphere for cooling. After being placed for cooling, the rolled copper foil as a sample for measurement is taken out from the seal. The sample surface of the heat-treated rolled copper foil is used as the measurement object, and a scanning electron microscope (SU-70) manufactured by Hitachi, Ltd. is used to measure the area ratio of the Cube orientation {001}<100> of the heat-treated rolled copper foil by the method described above. It should be noted that in Tables 1, 2, and 3, the arithmetic mean of the area ratio of the Cube orientation {001}<100> measured at 3 points (any point N1, N2 at a distance of 5 mm from N1 in the direction perpendicular to the rolling, and point N3 at a distance of 5 mm from N1 in the direction perpendicular to the rolling and in the direction opposite to the direction from N1 to N2) avoiding abnormal parts is shown as the Cube area ratio. The arithmetic mean is calculated from the values ​​rounded to the first decimal place by rounding off the second decimal place of N1 to N3, and is similarly expressed by the value rounded off to the second decimal place. It should be noted that for the rolled copper foil after the final cold rolling and before the heat treatment at a heating holding temperature of 370°C and a heating holding time of 1 second, an attempt was made to measure the Cube area ratio in the same manner. However, since the size of the subgrains and dislocation cell structures in the rolled structure was smaller than the step size (3 μm) of the EBSD measurement conditions, it was not possible to measure under the same conditions as the measurement conditions of the sample of the rolled copper foil after the heat treatment.

[0201] [Table 1]

[0202]

[0203]

[0204] (Examination of Example 1)

[0205] Comparing Examples 1 to 4 with Comparative Examples 1 to 3, it was found that, on the basis of the final cold rolling processing degree being greater than 98% and less than 99%, by appropriately setting the average grain size after the final annealing, it was confirmed that the arithmetic mean of the Cube area rate of the rolled copper foil when heat-treated at a heating holding temperature of 370°C and a heating holding time of 1 second could be increased. It should be noted that the arithmetic mean of the Cube area rate of N1 to N3 in Examples 1 to 4 is all above 80.0%. Therefore, it can be inferred that the arithmetic mean of the Cube area rate of the rolled copper foil when heat-treated under the specified conditions is above 80.0%, except for the abnormal parts on the surface.

[0206] (Reference Examples 1 to 4, Comparative Example 4)

[0207] <IPC sliding bending test>

[0208] In reference examples 1 to 3, in order to confirm the relationship between the arithmetic mean of the Cube area ratio and the bendability in the CCL, rolled copper foils having the Cube area ratios described in Table 2 when subjected to heat treatment at 360°C for 30 minutes were prepared. Next, a portion of the rolled copper foil before the heat treatment at 360°C for 30 minutes, i.e., after the final cold rolling, was taken as a sample for measurement. On the surface of one side of the sample for measurement, after roughening plating treatment was performed with reference to the above-mentioned roughening plating treatment conditions, Pixio (trademark) FRS grade (thickness 25 μm) manufactured by Kaneka Co., Ltd. as a polyimide resin film was laminated on the roughening plating treatment side of the rolled copper foil, and pressed by hot pressing treatment at 360°C for 30 minutes, thereby producing a single-sided copper-clad laminate consisting of two layers of rolled copper foil and polyimide resin film.

[0209] In addition, in Reference Example 4 and Comparative Example 4, a rolled copper foil having a Cube area ratio as described in Table 3 when subjected to a heat treatment at 340°C for 1 second was prepared. Next, a portion of the rolled copper foil before the heat treatment at 340°C for 1 second, i.e., after the final cold rolling, was taken as a sample for measurement. On the surface of one side of the sample for measurement, a roughening plating treatment was performed with reference to the above-mentioned roughening plating treatment conditions, and then, on the roughening side of the rolled copper foil, two rolled copper foils were laminated in a manner of sandwiching a polyimide resin film of Pixio (trademark) FRS grade (thickness 25 μm) manufactured by Kaneka Co., Ltd., and pressed by lamination at 340°C for 1 second, thereby preparing a double-sided copper-clad laminate consisting of three layers of rolled copper foil, polyimide resin film, and rolled copper foil. After the pressure bonding, the rolled copper foil on the lowermost layer side of the double-sided copper-clad laminate was completely removed by etching to prepare a single-sided copper-clad laminate consisting of two layers of the rolled copper foil and the polyimide resin film.

[0210] Then, for the single-sided copper-clad laminates of Reference Examples 1 to 4 and Comparative Example 4, known photolithography techniques were used to form circuits in a manner where the circuit width (Line) of the copper foil and the spacing (Space) between adjacent circuits were Line / Space = 300 μm / 300 μm, and FPCs were made respectively. Next, a test piece was cut from the obtained FPC in a manner where the width was 12.7 mm, the length was 130 mm, and the length direction of the test piece was parallel to the rolling direction. Figure 2 The IPC (Association of Printed Circuit Industries) bending test device 200 shown in the figure performs IPC sliding bending measurements on these test pieces. The IPC bending test device 200 is a structure in which a vibration transmission component 220 is combined with a vibration driving body 210. The test piece 230 is fixed to the device at a total of four points, namely, the portion of the screw 240 indicated by the arrow and the top portion of the vibration transmission component 220. When the vibration transmission component 220 is driven up and down, the middle portion of the test piece 230 is bent into an arc shape with a specified curvature radius r. The IPC sliding bending test is carried out under the conditions of a curvature radius r of 2.5 mm (outer radius), a vibration stroke of 20 mm, and a vibration speed of 1500 times / minute.

[0211] It should be noted that in the IPC sliding bending test, the number of times until the bending is repeated under the above conditions is counted, and the number of trials under each condition is set to 4 times, and the IPC sliding bending test is implemented. The average value of the number of times until the breakage is recorded as IPC sliding bending and is shown in Table 2 and Table 3 respectively. It should be noted that the breakage mentioned here means that the electrical impedance of the FPC before the IPC sliding bending test has increased by 20%. The electrical impedance is measured by a 4-terminal method.

[0212] [Table 2]

[0213]

[0214] [Table 3]

[0215]

[0216] (Examination of Example 2)

[0217] Based on the comparison of the results obtained in Reference Examples 1 to 4 and Comparative Example 4, it can be confirmed that when a CCL with a rolled copper foil having a high arithmetic mean of the Cube area ratio is used to make an FPC, it has better bendability than before. In addition, surprisingly, when the arithmetic mean of the Cube area ratio is 77.0% or more, the result of a sharp increase in bendability is obtained (refer to Figure 3 ). That is, it can be seen that if the arithmetic mean of the Cube area rate is 77.0% or more in the manufacture of CCL using the lamination method, the bendability can be greatly improved. It should be noted that according to the research of the inventors, it is known that in a short-time heat treatment such as the lamination method, the higher the heat treatment temperature, the faster the heating rate of the rolled copper foil, the formation and growth of multi-directional oriented crystal nuclei, there is a tendency to suppress the development of the cube orientation, and the Cube area rate is easy to decrease. Therefore, in the lamination method, if the arithmetic mean of the Cube area rate on the surface of the rolled copper foil can be made to be 77.0% or more by performing a heat treatment at a relatively high temperature of 370°C for 1 second, then even if the heat treatment temperature of the lamination method changes within the tolerance range, the manufactured CCL, and then the FPC manufactured using the CCL, can also be expected to have better bendability than before.

[0218] Explanation of symbols

[0219] 100: Fixture

[0220] 110: First clamping part

[0221] 112: 1st clamping surface

[0222] 114: Surface

[0223] 116:Handle

[0224] 120: Second clamping part

[0225] 122: Second clamping surface

[0226] 130: Hinge

[0227] 200:IPC bending test device

[0228] 210: Vibration drive body

[0229] 220: Vibration transmission component

[0230] 230: Test piece

[0231] 240:Screw

[0232] r: radius of curvature

Claims

1. A rolled copper foil containing 99.9 mass % or more of Cu, the remainder being inevitable impurities, wherein when the rolled copper foil is heat treated at a heating holding temperature of 370° C. and a heating holding time of 1 second, the arithmetic mean of the cube area ratio obtained by measuring an arbitrary point and two points in a direction perpendicular to the rolling and being equally spaced 5 mm from the point, that is, a total of three points, is 77.0% or more. 2 . The rolled copper foil according to claim 1 , further comprising 180 to 360 mass ppm of Ag.

3. The rolled copper foil according to claim 1 or 2, which has a thickness of 4 to 35 μm.

4. A copper-clad laminate comprising a rolled copper foil having a Cube area ratio of 77.0% or more. 5 . A method for producing a copper-clad laminate, comprising the step of bonding the rolled copper foil according to claim 1 to a substrate, and performing a heat treatment in the step. 6 . A method for manufacturing a flexible printed wiring board, comprising the step of using the copper-clad laminate manufactured by the method for manufacturing a copper-clad laminate according to claim 5 as a material to form a circuit.

7. A method for manufacturing an electronic component, comprising the step of manufacturing an electronic component including a flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board according to claim 6.